O Trombone na música de câmara para metais na Paraíba: um levantamento histórico (1980 – 2010) - Oliveira, Sandoval Moreno de (2012)
The objective of this work is to present the universe of chamber music for brass instruments with emphasis on trombone, showing particularly its contribution in the following groups from Paraíba, from 1980 to 2010: Brass'il Metal Quintet, UFPB Trombone Quartet, Northeast Brass Instruments Group, Trombone Quartet of Paraíba and Brazilian Trombone Ensemble. To have a clear understanding of the trombone in brass chamber music, a historical survey through systematic bibliographic, documentary, and private collection research is conducted. The context and particularities of chamber music in Brazil and Paraíba state and the history of trombone are discussed. An analysis of the activities and concert programs of the studied groups is made. Written and arranged works with the participation of the trombone, which allow a broad view of chamber music for the trombone in Paraíba state, are presented .